2009
DOI: 10.1186/1476-4598-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RRM2 decreases thrombspondin-1 and increases VEGF production in human cancer cells in vitro and in vivo: implication of RRM2 in angiogenesis

Abstract: Background: In addition to its essential role in ribonucleotide reduction, ribonucleotide reductase (RNR) small subunit, RRM2, has been known to play a critical role in determining tumor malignancy. Overexpression of RRM2 significantly enhances the invasive and metastatic potential of tumor. Angiogenesis is critical to tumor malignancy; it plays an essential role in tumor growth and metastasis. It is important to investigate whether the angiogenic potential of tumor is affected by RRM2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 33 publications
(62 reference statements)
3
86
0
Order By: Relevance
“…As we all know, relationships of annotation terms in one cluster have similar annotation contents and correlative functions. Some researchers indicated that overexpression of RRM2 significantly enhances the invasive and metastatic potential of tumor [1,32]. Therefore, we deduced the weaker RRM2 phosphoprotein function in HCC consistent with our above computation.…”
Section: Discussionsupporting
confidence: 75%
“…As we all know, relationships of annotation terms in one cluster have similar annotation contents and correlative functions. Some researchers indicated that overexpression of RRM2 significantly enhances the invasive and metastatic potential of tumor [1,32]. Therefore, we deduced the weaker RRM2 phosphoprotein function in HCC consistent with our above computation.…”
Section: Discussionsupporting
confidence: 75%
“…Although only three patients were assigned to the PR molecular subtype, the hazard for TTT was 9-fold the average, identifying a subset of patients with imminent progression, as also reported by Hose et al 32 The top gene in the GEP4 model, RRM2, is the beta subunit of ribonucleotide reductase (RNR). RRM2 overexpression is associated with cellular invasiveness, metastasis and tumor angiogenesis 33 via activation of the ERK1/2 signaling pathway 34 in cancer. RRM2 expression independently identified 15.2% patients with a 2-year TTT estimate of 75% (Online Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…20 Overexpression of RRM2 has been associated with increased invasion, angiogenesis, and metastasis. 21 In addition, overexpression of RRM2 in pancreatic adenocarcinoma has been found to induce MMP9, 22 which demonstrated a 3.33-fold increase in expression in tumor-adjacent compared with distant adipose tissue. Increased levels of MMP9 have been found on M2 macrophages and are induced in promonocytes when co-cultured with breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%